Development of Leuwidingding Village as a Tourist Village Through Agro-Edu-Tourism Concept - Syiafudin, Ahmad; Nurhidayanti, Nurhidayanti; Septiyani, Dwi; Kartini, Eneng; Yusani, Anisa (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
Tourism is currently a hype in the life of modern society. The tourism village model is a trend of alternative tourism development in Indonesia that continues to increase in popularity. Desa Leuwidingding is one of the villages that has the potential to be developed as an agricultural-based tourism village. The natural resources and superior potential found in Desa Leuwidingding are worth utilizing and developing sustainably. However, the number of visitors who come is still relatively low because the construction has not been optimized and stopped during the COVID-19 pandemic. Through community service activities, as a form of participation in the development of the tourism village, students create a work program that carries the concept of